PATH-22. GENETIC VARIATION BETWEEN IDH MUTANT AND IDH WILD-TYPE GLIOMA. (12th November 2021) - Li, shaoqun; Lai, Mingyao; Zhou, Jiangfen; Zhen, junjie; Cai, Linbo
Abstract: OBJECTIVE: The prognosis of IDH mutant glioma was significantly different from that of IDH wild-type glioma. In order to explore the differences between them at the genetic level, we analyzed the genetic results of IDH mutant and IDH wild-type glioma. METHODS: This study analyzed the clinical data and genetic results of 45 glioma patients from Jan. 2017 to Dec. 2019, exploring relevant prognostic indicators and the difference in genetic profile between IDH mutant glioma and IDH wild-type glioma. RESULTS: 45 patients were included in this study, including 15 IDH mutant glioma patients and 30 IDH wild-type glioma patients. Genetic analysis showed that there was no difference in tumor mutation burden (TMB) and microsatellite instability (MSI) between IDH mutant glioma and IDH wild-type glioma. But somatic mutation between IDH mutant and IDH wild-type glioma was different. The expressions of IDH1, CIC, SYNE1 and TP53 were different in the two groups, among which IDH1 and CIC were more significantly different. Copy number variations (CNV) was also different between IDH mutant glioma and IDH wild-type glioma. STIL occured more frequently in IDH wild-type gliomas. Genetic analysis also showed the difference in variant allel frequence (VAF). IDH mutant gliomas were more likely to be combined with ATRX and TP53 mutations, while IDH wild-type gliomas, in addition to the combination of TP53 mutations, often also combined with the mutations of NF1, BRAF and PTEN. In survival analysis, glioma with IDH mutation has a good prognosis, and IDH wild-type patients have a poor prognosis. In IDH wild-type patients, patients with PTEN mutation have a worse prognosis. CONCLUSION: There is an obvious genetic difference between IDH mutation and IDH wild-type glioma, and PTEN mutation is a poor prognostic factor for IDH wild-type patients.